(untitled) (Revista Contexto & Saúde, 2026)
The aim of this study was to design efficiency requirements for the development of a technological device to be used in patient transport in conventional elevators with reduced cabin dimensions. This methodological study was conducted from October 2021 to December 2022 and comprised five phases: scoping review; mapping of influencing factors and identification of requirements; definition of requirements; content validity using the Content Validity Index (CVI) by an expert committee; and synthesis and analysis of information and data. Twenty experts, including physicians, nurses, military firefighters, and a Franco-Brazilian firefighter (Paris), from the five Brazilian macro-regions (North, Northeast, Midwest, Southeast, and South), responded to a validity instrument developed using a Likert scale. Among the results, 90% of items reached the recommended level of agreement and satisfaction, considering values above 0.8 (CVI values between 0.8 and 1). Only one item obtained a CVI of 0.55 and was therefore considered statistically inadequate and excluded. Four items were added based on experts’ suggestions. Additionally, ten technological devices for patient transport available in national and international markets were analyzed for benchmarking purposes, as they presented specifications closest to the established requirements, although none fully met all properties and characteristics. This study identified an opportunity to develop a new technological solution that is practical, applicable, accessible, and low-cost, as a health technology aimed at optimizing patient transport in pre-hospital care services in Brazil.